Lung Scanning with the Gamma Camera, Using Complexes of 99mTc-Sulphur Colloid and Macroaggregated Human Serum Albumin - Weber, Theodor H.; Nordman, Clas T. (Nuklearmedizin - NuclearMedicine, 1971)
The results of lung scanning in suspected pulmonary embolism, using the gamma camera and complexes of 99mTc-sulphur colloid and macroaggregated human serum albumin are presented. In a series of 52 patients excellent scanning images were obtained in each case, without any adverse side effects. The preparation of the test substance takes about 20 minutes and can be performed routinely by a laboratory technician. The use of a gamma camera in connection with this test substance allows anterior, posterior and lateral view scanning to be performed within 15 minutes, with minimal strain on the patients. Multipleview scanning is shown to be necessary in screening for pulmonary embolism.